Re-assessing the Triadic Model of Care for Trans Patients Using a Harm-Reduction Approach. - Gruenewald, A. F. (Health Care Analysis, 2020)
The World Professional Association for Transgender Health's Standards of Care (WPATH SOC), now in its seventh edition, is a frequently cited, internationally recognized, evidence-based document that details a comprehensive framework for gender-related care of trans people. However, the WPATH SOC still relies heavily in some cases on gatekeeping practices, dubbed "triadic therapy," or a process where a trans patient is encouraged to seek out psychotherapy, and hormone therapy, and only then be able to engage in surgical options for transitioning. I use G. Alan Marlatt's harm reduction framework to argue that the triadic process creates its own set of harms that trans people have to contend with, especially insofar as it focuses on resolving gender dysphoria in a demanding, moralizing, and top-down way as opposed to enriching trans lives by reducing harms that prevent us from flourishing. Using Marlatt's criterion that harm reduction ought to be bottom-up, low threshold, and not moralizing, I develop a list of suggestions for what ought to be centrally considered in treating trans patients.